Implementasi Spiritualitas Belas Kasih dalam Pelayanan Klinik Pratama Tabita Gunungsitoli - Valentina Yuliba Ndruru; Alfons Seran; Dominikus Doni Ola (Journal New Light, 2025)
This article discusses the implementation of spirituality of mercy at the Klinik Pratama Tabita Gunungsitoli. Mercy is at the heart of the gospel of Jesus Christ and the Church's calling. Mercy is the foundation of God's discipleship spirituality and is a characteristic of the way of life and the way of serving the medical staff at the Klinik Pratama Tabita Gunungsitoli. The motivation of the author in this study is that nowadays there is a tendency for humans not to build a culture of mercy. Planet earth as a home for human beings is felt uncomfortable and safe due to various acts of violence, injustice, discrimination, intolerance, ethical violations, and natural disasters. All of this indicates that humans live without mercy. This research is qualitative research with Appreciative Inquiry approach called the 4D process, namely discover, dream, design, and destiny. Using this research method, the researcher will get data directly from the respondents themselves about their experiences about the recognition, understanding and living out of mercy spirituality at the Klinik Pratama Tabita Gunungsitoli. From the study, it was found that the majority of medical professionals know, understand and living out the spirituality of mercy in life, especially in serving patients at the Klinik Pratama Tabita Gunungsitoli. The significant thing from their experience is that there are ten characteristics of mercy that animate their way of life and the way they serve patients, namely sympathy, hospitality, generosity, simplicity of heart, humility, willingness, sacrifice and selflessness.